(untitled) (FUDMA JOURNAL OF SCIENCES, 2023)
Respiratory syncytial virus (RSV), also known as a human respiratory syncytial virus (hRSV) and human orthopneumovirus, is a common, transmittable virus that roots respiratory tract diseases. It is a negative-sense, single-stranded Ribonucleic acid (RNA) virus. It gets its name from syncytia, which are huge cells that form when infected cells merge. In this paper fractional order model of the respiratory syncytial virus (RSV) virus will be developed. The Caputo fractional derivative operator of the order will be used to generate the model scheme of non-integer differential equations. To calculate an estimated solution of the system of nonlinear fractional differential equations, the Laplace-Adomian Decomposition Method was used. Infinite series was produced as solutions to fractional differential equations. The model’s proposed series solution converges quickly to its precise value. The obtained results are compared to the standard case.